2016
DOI: 10.1183/13993003.01011-2016
|View full text |Cite
|
Sign up to set email alerts
|

Mortality prediction in idiopathic pulmonary fibrosis: evaluation of computer-based CT analysis with conventional severity measures

Abstract: Computer-based computed tomography (CT) analysis can provide objective quantitation of disease in idiopathic pulmonary fibrosis (IPF). A computer algorithm, CALIPER, was compared with conventional CT and pulmonary function measures of disease severity for mortality prediction.CT and pulmonary function variables (forced expiratory volume in 1 s, forced vital capacity, diffusion capacity of the lung for carbon monoxide, transfer coefficient of the lung for carbon monoxide and composite physiologic index (CPI)) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
203
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 239 publications
(215 citation statements)
references
References 41 publications
8
203
2
2
Order By: Relevance
“…CALIPER CT analysis has been previously described (29,31), and is outlined in the Supplementary appendix.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…CALIPER CT analysis has been previously described (29,31), and is outlined in the Supplementary appendix.…”
Section: Methodsmentioning
confidence: 99%
“…New computer algorithms utilising three-dimensional volumetric CT datasets, can quantify parenchymal pattern extents (27,28) and have been shown to better predict survival in various fibrosing lung diseases at baseline, than visual CT scores (29,30). Computer analysis also has the potential to uncover CT features hitherto under-recognised by visual CT analysis that predict mortality in IPF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigators also found that a novel parameter called pulmonary vessel volume (PVV) had stronger correlations with lung function tests, indicating that it may have potential in assessing disease severity in IPF. The same group demonstrated that CALIPER-derived honeycombing and PVV were more accurate than traditional fibrosis scores in predicting mortality, independent of physiological indices [75]. While quantitative disease assessment in lung fibrosis has been around for some years, its application in monitoring disease in therapeutic trials has recently gained interest.…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…These difference confirmed both derivation cohort and validation cohort. (Table 1) This index is simple and applicable not only tertiary center but also general hospital (52,53).And GAP index was valuable as a measure of IPF severity (54)(55)(56)(57)(58)(59). Presence of Velcro Crackles is associated with high score of GAP in IPF (60).…”
Section: Chronic Phasementioning
confidence: 99%